Experimental Results on the Fixed Matrix Regenerator Effectiveness for a Glass Stove Furnace. Issue 6 (12th April 2016) - Wołkowycki, Grzegorz
Abstract : This paper presents experimental results on the effectiveness of regenerators working integrally with an open hearth glass furnace. The presented data refer to two apparatus of identical size and geometry arranged in parallel but operating in a one-period-shifted mode. The effectiveness figures with corresponding uncertainties for each unit have been determined by making use of experimental data accounting for both heating and cooling periods. For the heating period the effectiveness is bound within the range 0.8795 ± 0.0683 to 0.9272 ± 0.0715. Considering those for the cooling period the effectiveness holds 0.9142 ± 0.0305 to 0.9499 ± 0.0329, shown to be accompanied by a bit lower uncertainty. Due to the difference in effectiveness, averaging was applied to calculate mean effectiveness value measured as weighted based on the uncertainties for both periods. As the result, the final averaged effectiveness of the investigated regenerators was found to be within the ranges of 0.9153 ± 0.0278 to 0.9367 ± 0.0296.